If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k * k = 36 Multiply k * k k2 = 36 Solving k2 = 36 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Simplifying k2 = 36 Take the square root of each side: k = {-6, 6}
| 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 | | 16-s=20 | | -6+w/3=-8 | | -36=p-01 | | 4a-4=-2 | | 5/1211/18 | | 3x^4-6x^3+3x^2=0 | | x(6-4)+3=15 | | f(m+3)=2m^2-2m+1 | | (3x+7)(x+5)=0 | | f=-18+-10x | | 16u^7x^6-7u^2x^6/-4u^3x^4 | | (x^2-3x+4)(2x-1)=0 | | f=-17+5x-1+-15x | | y/3+y | | 8-m=20 | | 15x^2y^3/25x^5y^3 | | 21x-14/4=-14 | | 1/2y+y | | 6(3y+5)=9 | | f(x)=-15x^2-17x+5 |